The Care Giver Lived Experience in Caring for Elderly With Palliative Conditions - Ni Komang Sukra Andini; Sang Ayu Ketut Candrawati (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Elderly is the final stage of the human development cycle. Every year the number of elderly people increases in Indonesia in the Bali area based on the population census. The prevalence of the number of elderly people from 2021 to 2022 increases. According to a survey by the Indonesian Medical Gerontology Association (PERGEMI), as many as 24.6% of the elderly population (seniors) in Indonesia have a history of chronic disease. In the condition of the elderly who are unable to take care of themselves fully, they need a caregiver or companion who is often called a caregiver, the role of a caregiver is as a provider of nursing care to the patient. Objectives: This study aims to describe of the care giver's experience in caring for elderly people with palliative conditions. Methods: Data were collected using the face-to-face individual in deep interview, with semi structure interview questions. Results: The results of this study by using interviews and observations from 4 participants, 4 themes were obtained that show the Care Giver's experience in caring for the elderly with palliative conditions, namely: (1) End Stage of Life Phase (2) Routine Care (3) Psychological Support (4) Spiritual Support. Conclusions: The description of the Care Giver's experience is considering palliative conditions as conditions in the End Stage of Life Phase; Daily care focuses on Routine Care; Psychological support is really needed; Spiritual support is really needed. Based on the research results, it can be concluded that elderly people in nursing homes in the final phase of their lived experience worsening conditions between life and death and all their needs are assisted by caregivers. In palliative conditions, all daily needs are fulfilled by the caregiver. The main focus of care for elderly people with palliative conditions is providing psychological support and spiritual supported